THE MEANING OF SOCIOLOGIY LEARNING WITH A TWO STRAY TYPE COOPERATIVE MODEL - Petrus Geroda Balawala; Idris (SocioEdu: Sociological Education, 2021)
This study is by the objective to know the meaning of teaching sociology with a model cooperative type of two strays. The method of research using the study of literature with 5 stages, collect literature and then do a review, collect the results of reviews of research relevant than 280 articles that obtained in google scholar, analyzed 30 articles were obtained and are considered relevant and the publication of which is at least 10 years past, to collate the results and discussion, conclusions and suggestions. The results of this study indicate that the two stray learning models can shape the competence of students. This can be seen from the changes that occur in students, namely being more active in arguing with their friends and students. Being more critical in communicating, thinking clearly, and rationally. Model two stray too can enhance the creativity of students in following the opportunity for students to share information to students other besides that too share information to students other. Besides that, also will instill a sense of togetherness to be better and be able to compete in the achievement of learning.